2019
DOI: 10.3389/fimmu.2019.02551
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling: Pathogen Incursion and Immune Defense

Abstract: Wnt ligands interact with the transmembrane cell surface receptors Frizzled and ROR/RYK to initiate complex signaling cascades that are crucial for cell physiology and the proper functioning of the immune system. Wnt signaling is instrumental in maintaining immune surveillance and during infections by pathogenic microbes helps mount host resistance to infection. Some pathogens, however, utilize Wnt signaling to build a niche for their survival. The goal of this review is to summarize current and developing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…In view of the role of Wnt5A signaling in actin assembly ( 16 , 24 , 27 , 28 ), we studied how the Wnt5A–Actin axis regulates the outcome of infection by a bacterial pathogen ( E. coli K1 isolate from a biliary sepsis patient) as compared to a non-pathogen (lab strain E. coli DH5α or E. coli K12-MG1655). The basis of pathogenicity and non-pathogenicity of these E. coli strains have already been documented ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the role of Wnt5A signaling in actin assembly ( 16 , 24 , 27 , 28 ), we studied how the Wnt5A–Actin axis regulates the outcome of infection by a bacterial pathogen ( E. coli K1 isolate from a biliary sepsis patient) as compared to a non-pathogen (lab strain E. coli DH5α or E. coli K12-MG1655). The basis of pathogenicity and non-pathogenicity of these E. coli strains have already been documented ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several labs including ours’ have demonstrated that Wnt5A signaling induces alterations in actin assembly in macrophages ( 16 , 24 , 27 , 28 ). This finding is in perfect agreement with the depicted role of Wnt5A in bacterial phagocytosis ( 15 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In brief, enriched GO terms characterized by upregulated DEGs were consistent with activation and mobilization of innate immune system factors, inflammation, host defense and wound healing. While prospective pathogen invasion pathways were connected to the downregulation of genes associated with wnt and integrin-mediated signaling as well as cell adhesion (59)(60)(61). GO categories were heavily enriched for downregulated genes in developmental process categories indicative of diverting metabolic resources away from growth.…”
Section: Local Host Responsementioning
confidence: 99%
“…Several other bacteria, mostly non-pathogenic commensals are also able to reside in macrophages without being killed (23,24). The idea one gets from several studies is that the fate of bacterial infections is associated with the cytoskeletal actin dynamics of macrophages (25)(26)(27). Despite considerable research in this field and extensive knowledge of the wide range of pathogenicity of several different bacteria our understanding of the molecular details of host macrophagebacteria interactions linked with infection outcome remains incomplete.…”
Section: Introductionmentioning
confidence: 99%